How should we define clinically significant improvement on Patient-Reported Outcomes Measurement Information System (PROMIS) for patients undergoing Knee Meniscal Surgery?...American Orthopaedic Society for Sports Medicine (AOSSM), 2020 Annual Meeting (Virtual). - Yining Lu; Nwachukwu, Benedict; Beletsky, Alexander; Patel, Bhavik; Yanke, Adam; Verma, Nikhil; Cole, Brian; Bush-Joseph, Charles; Bach, Bernard; Okoroha, Kelechi; Forsythe, Brian (Orthopaedic Journal of Sports Medicine)
Objectives: The Patient-Reported Outcomes Measurement Information System (PROMIS) attempts to optimize patient reported outcome (PRO) instruments by utilizing item response theory (IRT) and computer adaptive testing (CAT). Relatively little is known about clinically significant outcome (CSO) improvements on the PROMIS Physical Function (PF) CAT. The objective of this study is to define the minimal clinically important difference (MCID), substantial clinical benefit (SCB) and patient-acceptable symptom state (PASS) of the PROMIS PF CAT in arthroscopic meniscal surgery. Methods: The PROMIS PF CAT, Short Form-12 Health Survey (SF-12 physical health [PCS] and mental health [MCS]), Veterans Rand-12 Health Survey (VR-12 physical health [PH] and mental health [MH]), and the Marx Activities Ratings Scale were administered pre- and post- operatively to patients undergoing arthroscopic meniscal surgery. Six months postoperatively, patients graded their knee function based on a domain-specific anchor question. Answers to the anchor questions were dichotomized to indicate achievement of SCB and MCID. A satisfaction anchor question was used to indicate achievement of PASS. Receiver operating characteristic (ROC) analysis determined the relevant psychometric values. Cutoff analysis was performed to find preoperative PRO scores predicting CSO achievement. Results: Sixty patients (N = 27, 45% female) were included, with mean age of 45.0 ± 14.0 years and average follow up of 24.0 + 1.2 weeks. The most common indication for knee arthroscopy was partial meniscectomy (N = 53; 88.3%) followed by meniscal repair (N = 7; 11.7%). MCID on PROMIS PF was calculated to be 2.08 (AUC: 0.75, 95% CI: 0.57 - 0.94). Net score improvement equivalent to achievement of SCB was found to be 7.41 (AUC: 0.77, 95% CI: 0.55 – 0.99). PASS was found to be 45.47 (AUC: 0.89, 95% CI: 0.79-0.99). Preoperative score below 37.6 on the PROMIS PF CAT predicted achievement of MCID (AUC: 0.76, 95% CI: 0.64-0.88), while scores above 41.7 predicted achievement of PASS (AUC: 0.76, 95% CI: 0.63-0.89). Absence of pre-existing arthritis and higher baseline functional status were also found to be statistically significant predictors of achieving CSOs. Conclusion: Our study defined MCID, SCB, and PASS, for the PROMIS PF CAT. We found that a pre-operative score below 37.6 was predictive for achieving a meaningful clinical change with surgery, while a pre-operative score above 41.7 was predictive of achievement of an acceptable post-operative health state.